2022
DOI: 10.3390/jpm12101720
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Intubation Using C-MAC Video Laryngoscope vs. Direct Laryngoscope While Wearing Personal Protective Equipment

Abstract: This study sought to determine whether the C-MAC video laryngoscope (VL) performed better than a direct laryngoscope (DL) when attempting endotracheal intubation (ETI) in the emergency department (ED) while wearing personal protective equipment (PPE). This was a retrospective single-center observational study conducted in an academic ED between February 2020 and March 2022. All emergency medical personnel who participated in any ETI procedure were required to wear PPE. The patients were divided into the C-MAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…GlideScope, King vision and McGrath MAC) with wearing level C PPE, but the overall ETI time tended to decrease in DL [31]. However, in a clinical study wearing the same level of PPE, the FPS rate of C-MAC VL was found to be higher than DL [42].…”
Section: Comparison Of Endotracheal Intubation Methods: Video Laryngo...mentioning
confidence: 89%
“…GlideScope, King vision and McGrath MAC) with wearing level C PPE, but the overall ETI time tended to decrease in DL [31]. However, in a clinical study wearing the same level of PPE, the FPS rate of C-MAC VL was found to be higher than DL [42].…”
Section: Comparison Of Endotracheal Intubation Methods: Video Laryngo...mentioning
confidence: 89%
“…Additionally, the FPS rate was significantly higher in the VL group (94.3% vs. 58.6%, p < 0.001) [ 21 ]. In a recently published study, performed on 756 patients intubated within the Emergency Department by emergency physicians in PPE, Kim et al demonstrated a significantly increased FPS rate when a C-MAC VL was used instead of a MAC DL (85.7% vs. 69.8%, p < 0.001) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both tools of VL and DL have been dedicated for use in patients with COVID-19, where the tracheal intubation is feasible. [148,149]. It is also noticed that the tracheal intubation procedure might be hampered by the personal protective equipment [150][151][152][153].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%